Jasper's Basic Mechanisms of the Epilepsies 2012
DOI: 10.1093/med/9780199746545.003.0009
|View full text |Cite
|
Sign up to set email alerts
|

Tonic GABAA Receptor–Mediated Signaling in Epilepsy

Abstract: Fast inhibitory signaling in the brain has conventionally been considered to be predominantly mediated by the vesicular release of GABA from presynaptic terminals onto postsynaptic GABAA receptors.1 Transient opening of such receptors results in a brief increase in postsynaptic permeability to Cl–, generating an inhibitory postsynaptic potential (IPSP) that reduces the probability of firing of the neuron. However, there is abundant evidence that GABA can also act relatively far from its site of release, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 82 publications
1
28
0
Order By: Relevance
“…Cope et al showed that GABA A ‐mediated tonic inhibition is increased in thalamocortical neurons in GAT‐1 knockout mice. Increased GABA A ‐mediated tonic inhibition can lead to neuronal hyperpolarization and burst pattern firing in thalamocortical neurons, which can promote the generation of spike‐wave discharges . Similarly, prolonged activation of GABA B receptors is known to stimulate low voltage‐activated (T‐type) Ca 2+ channels, which can cause recurrent excitation within the thalamocortical system through successive Na + spikes .…”
Section: Discussionmentioning
confidence: 99%
“…Cope et al showed that GABA A ‐mediated tonic inhibition is increased in thalamocortical neurons in GAT‐1 knockout mice. Increased GABA A ‐mediated tonic inhibition can lead to neuronal hyperpolarization and burst pattern firing in thalamocortical neurons, which can promote the generation of spike‐wave discharges . Similarly, prolonged activation of GABA B receptors is known to stimulate low voltage‐activated (T‐type) Ca 2+ channels, which can cause recurrent excitation within the thalamocortical system through successive Na + spikes .…”
Section: Discussionmentioning
confidence: 99%
“…The perception of δ‐containing GABA A receptors as therapeutic targets for retigabine leads to the pathophysiology of such receptors in epilepsy. In various models of temporal lobe epilepsy, δ subunit expression and functions of extrasynaptic GABA A receptors undergo complex changes . Loss of neurosteroids that activate δ‐containing GABA A receptors increases seizure frequency, whereas overexpression and activation of extrasynaptic GABA A receptors reduces seizure‐like activity in vitro and in vivo, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…This, however, does not hold true for all types of seizures. Enhanced activity of extrasynaptic GABA A receptors in thalamocortical neurons is a common pathophysiologic mechanism in several models of absence epilepsy, and absence seizures are exacerbated by drugs that activate δ‐containing GABA A receptors . Retigabine has been found to be effective in virtually all types of seizure models, with the notable exception of absence seizures, even though Kv7 channels are highly expressed in the thalamus .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the functional difference between mGAT1 and mGAT3/4 prompts a refinement of therapeutic targets for drugs acting on the GABA uptake systems. For example, the anti-epileptic drug, tiagabine, a mGAT1 blocker, increases GABA spillover, and can affect the time course of IPSCs (Walker and Kullmann, 2012). Because IPSCs are involved in synaptic computations, tiagabine can potentially have unwanted effects on synaptic network operation.…”
Section: Discussionmentioning
confidence: 99%